Peran Pembiayaan Perbankan dan Government Support Melalui Finance Behavioral Untuk Meningkatkan Kinerja UKM - Sudarnice Sudarnice; Andry Stepahnie Titing; Titin Juniarti (ASSET: Jurnal Manajemen dan Bisnis, 2025)
So that SMEs can remain competitive in an unstable market circle, in the digital era, especially after the current COVID-19 pandemic crisis, SME performance needs to be improved. Therefore, the main objective of this research is to identify the influence in improving SME performance through the relationship between government encouragement variables and bank relationships on SME performance with the mediating role of financial behavior. The method applied in the research starts from data collection, the researcher took a list of SMEs as a sample frame using characteristics that have relationships with banks and the government. Data was obtained by distributing questionnaires to 115 SME owners and supported by several interviews with SME owners due to respondents' lack of understanding of the variables we used, then factor analysis was carried out using the Principal Component Analysis method. The data analysis method used in this research also uses Structural Concept Equation Modeling (SEM) with the Partial Least Square (PLS) program. The research results show that SME performance is not directly influenced by bank relationships and government support, but there is an indirect influence through financial behavior